Anxiety, depression and risk of cannabis use: examining the internalising pathway to use among Chilean adolescents - Stapinski, Lexine A; Montgomery, Alan A.; Araya, Ricardo (Elsevier, 2016)
Background: Adolescents who experience internalising symptoms may be susceptible to the use of alcohol and other substances in an attempt to alleviate or cope with these symptoms. We examined the hypothesised internalising pathway from symptoms of depression, generalised anxiety, social anxiety and panic, to incidence and frequency of cannabis use 18 months later. Method: Longitudinal cohort study of participants (n = 2508; 45% female; mean age 14.5 years) recruited from the 9th grade at 22 low-income secondary schools in Santiago, Chile. Baseline internalising symptoms were assessed using the Beck Depression Inventory and the Revised Child Anxiety and Depression Scale. Frequency of cannabis was assessed at baseline, 6 month and 18 month follow-up. Results: High rates of use were observed in this sample, with 40.3% reporting cannabis use at least once over the study period. Adjusted for baseline cannabis use, symptoms of depression, panic and generalised anxiety were associated with greater cannabis use frequency 18 months later. When all predictors were considered simultaneously, only generalised anxiety symptoms showed an independent association with subsequent cannabis use frequency (OR: 1.23, 95% CI: 1.08–1.41). Generalised anxiety symptoms were also associated with a 25% increased risk of transitioning from non-user to use of cannabis during the study (OR: 1.25, 95% CI: 1.09–1.44). Conclusions: Internalising symptoms, and in particular symptoms of generalised anxiety, increase risk of cannabis use during adolescence. Targeted interventions that promote adaptive anxiety management among high-risk adolescents may represent a promising strategy to prevent uptake of cannabis use during adolescence.